The impact of the leadership styles on crisis management: A study at Yemen private and public institutions - Alkhawlani, Mohammed Ali Saleh (2016)
Crisis management plays an essential role in an organization to conduct its daily activities, where crisis has to be managed. However, choosing the proper leadership style is the main challenge to avoid disastrous consequences during the current crisis situation in Yemen. Therefore, the main objective of the study was to determine the influence of leadership styles in terms of transformational, transactional and charismatic leadership styles on crisis management in the Yemeni private and public institutions. The study further aimed to determine the most influential leadership style on crisis management. In order to achieve the objectives of the study, a quantitative method was applied and the data were collected from 297 middle managers in the Yemeni private and public institutions. Regression test was used to investigate the relationship between the leadership styles and crisis management as well as to determine the most influential leadership styles on crisis management. The results indicated that transformational, transactional and charisma leadership styles were found to have positive influences on crisis management. Furthermore, the results also indicated that transactional leadership was the best predictor and the most influential factor on crisis management in Yemeni private and public institutions. This was followed by charisma and transformational leadership styles, respectively. Overall, this study has provided a valuable contribution to the body of knowledge in the fields of leadership styles and crisis management. Future research is recommended to focus on the dimensions of the transformational leadership styles and crisis management stages for more specific outcomes.